The Prevalence of Undiﬀerentiated Connective Tissue Dysplasia in Senior Students - Mykhailo Protsailo; Volodymyr Dzhyvak; Ihor Krycky; Pavlo Hoshchynskyi; Ihor Horishnyi; Iryna Chornomydz (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. Connective tissue dysplasia is an important medical condition requiring attention and research.